Employee Loyalty at Bank BNI KCU Garut is Impacted by Work Discipline and Career Development - Sonia Meidiana Dimyati; Ayuningtyas Yuli Hapsari (Universitas Pamulang, 2023)
Because employees' potential must be able to be developed by the company, human resource management is a division that plays a role in developing the potential of every employee in the organization. Employees must always comply with the firm's policies and apply the applicable norms, and the organization must provide career growth to every employee with potential and achievement. Employee loyalty at Bank BNI KCU Garut should improve as a result of these two factors. The purpose of this research is to find out how to work discipline, career growth, and employee loyalty are affected by work discipline at Bank BNI KCU Garut. This study aims to determine how to work discipline, career development, and employee loyalty are related at Bank BNI KCU Garut, as well as to determine how to work discipline affects employee loyalty at Bank BNI KCU Garut, and how career development affects employee loyalty at Bank BNI KCU Garut, as well as to determine how the simultaneous influence of work discipline and career development on employee loyalty at Bank BNI KCU Garut. The descriptive and verification methodologies were utilized in the research. The population of this study is all employees at Bank BNI KCU Garut, whereas the sample is some employees at Bank BNI KCU Garut. Path analysis and hypothesis testing are used to process data. Based on the findings of the study, it can be concluded that work discipline has an impact on employee loyalty at Bank. BNI KCU Garut and the simultaneous influence of work discipline and career development on employee loyalty at the Bank BNI KCU Garut and the simultaneous influence of work discipline and career development on employee loyalty at the Bank Garut BNI KCU.